Dėl latvių senųjų tekstų vienaskaitos lokatyvo - Rosinas, Albertas (Baltistica, 2001)
ON THE LOCATIVE SINGULAR IN OLD LATVIAN TEXTS On the basis of the data from Latvian old texts, the article proves that in the 16th –17th centuries there existed two locative singular forms in the Latvian language: the old inessive in -ā, -ē, -ī, -ū and the illative in -an, -en, -in, -un whose meanings were neutralized. The forms in question belonged to the same declension system. To assume that there were two declension systems, one with the generalized inessive and the other with the generalized illative (as is stated by Pēteris Vanags), and to maintain that the inessive endings in -ā, -ē, -i, -ū evolved phonetically from the illative forms in -an, -en, -in, -un, one needs more substantial evidence, for there exist the demonstrative pronominal illative and inessive forms tan and tanī. The tan-type forms mentioned above could not have survived in the first system, whereas in the second system, according to Vanags’ Law, they should have become *tā-type forms. Following this reasoning, tanī -type forms could not have occurred in either system. As can be seen from the Latvian textual data of an earlier period, the locatives of illative origin, which also performed the function of the inessive in Latvian texts, were ousted from the language system. Their disappearance was caused by two major principles of morphological evolution: (1) m͐ > m͑; (2) in the course of inner morphological changes, in the competition between less-marked and more-marked forms, the less-marked form is preserved. The inessive was such a less-marked form.